Thematic differentiation of loanwords in the newspaper “Kazakhstanskaya Pravda” - Balabekova, М.А.; Vesselinov, D. ("Акад. Е.А. Бөкетов ат. Қарағанды ун-ті" КЕАҚ баспасы, 2023)
As a result of language contacts in the lexical system of the Russian language, borrowed vocabulary builds a new class of words. The study of linguistic convergence, which determines the process of borrowing and further adaptation of foreign vocabulary, cannot take place in isolation from the fact of the influence of the norms of one language system on another. This article is devoted to the study of borrowed words in media texts. The purpose of this work is the implementation of a comprehensive linguistic study of the mechanisms of language convergence and the analysis of new words functioning in the mass media of Kazakhstan. The material of the study is the newspaper “Kazakhstanskaya Pravda” of 2018. 5000 borrowed words were written out and analyzed by the continuous sampling method. All borrowings are divided into two groups — “mode of life” and “education”. A large percentage difference indicates that political, economic relations and the development of the business industry and technology are gaining the main positions in the group “mode of life”. Based on the analysis of the proofreading of loanwords 47 thematic groups were derived on the pages of newspapers. The classification of thematic groups shows us in which spheres of society borrowed words are in great demand and function. The most frequently used words and terms were related to politics, economics, business, medicine, profession, quality, art, technology, Internet and psychology.
«Казахстанская правда» газетіндегі кірме сөздердің тақырыптық айырмашылығы
Тематическая дифференциация заимствований в газете «Казахстанская правда»
Keywords: borrowings; language convergence; English language; language contacts; mass media; Kazakhstanskaya Pravda; contactology